CLINICAL MANIFESTATION APPROACH OF DENGUE VIRAL INFECTION - Tjahjono, Ganis; Widiyanti, Prihartini; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2016)
Currently by an estimated 50-100 million dengue fever cases per year in worldwide, 500.000 were in the form of a disease is heavy Dengue Hemorraghic Fever (DHF) and Dengue Shock Syndrome (DSS). Survey serology in Indonesia show that DEN-1 and DEN-2 are the dominant serotipe virus until the end of the 1980s but the recent shift has occurred epizoötic where viruses DEN-3 dominant. (Dos Santos, 2004; Malavige, 2004; Stephenson, 2005). Dengue virus infection induces transient immune aberrant activation of CD4/CD8 ratio inversion and cytokine overproduction, and infection of endothelial cells and hepatocytes causes apoptosis and dysfunction of these cells. The aberrant immune responses not only impaire the immune response to clear the virus, but also result in overproduction of cytokines that affect monocytes, endothelial cells, and hepatocytes. Dengue-virus-induced vasculopathy and coagulopathy must be involved in the pathogenesis of hemorrhage, and the unbalace between coagulation and fibrinolysis activation, and prolonged duration of shock increase the likelihood of severe hemorrhage in DHF/DSS. Capillary leakage is triggered by the dengue virus itself or by antibodies to its antigen. To date, there are no effective strategies to prevent the progression of DHF/DSS. The control of dengue will be possible only after an efficient vaccine has been developed.